Effect of Perioperative Administration of Tranexamic Acid on Postoperative Bleeding Following on Pump CABG - Shahidullah, AYM; Rahim, AM Asif; Hossain, ASM Iftekher; Islam, Syed Monirul; Bari, Md Sajedul; Hosain, Nazmul (Cardiovascular Journal, 2019)
Background: One of the main causes of post-operative morbidity in cardiac surgical patient is excessive bleeding requiring transfusion of blood component after CPB. Re-exploration due to bleeding occurs in 2% to 7% of post bypass patient and 50% to 80% of these patients not having any identifiable surgical bleeding source. Tranexamic acid is competitive inhibitor of plasminogen activator and at higher concentration a non-competitive inhibitor of plasmin. It is 10 times more potent than Epsilone Aminocaproic Acid in preventing post-operative haemorrhage following CPB. Methods: This study was conducted in the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh between January 2009 and December 2010. The Study population was divided into two groups. Group A comprised of 35 patients, who had received Tranexamic Acid 10 mg /kg after induction and then 1 mg/kg/hour till time of protamin infusion and Group B comprised of 35 patients who had received same amount of normal saline 0.9% NaCl as placebo. Results: The postoperative bleeding during both 1 to 4 hours and 4 to 24 hours was significantly lower in the Tranexamic Acid group as compared to the placebo group (p value <0.001). There was no significant difference between groups in terms of platelet count and prothrombin time. Conclusion: From the study, we conclude that “Perioperative Administration of Tranexamic acid reduces post operative bleeding and also reduces the need for postoperative blood transfusion in CABG patents using Cardiopulmonary bypass”. Therefore it is recommended that routine prophylactic use of Tranexamic Acid should be carried out to decrease the postoperative hemorrhage and requirement blood transfusion. Cardiovasc. j. 2019; 12(1): 20-23